An investigation of shariah penny stocks’ performance and its determinants: Evidence from Bursa Malaysia - Che Ismail, Che Muhamad Hafiz; Adewale, Abideen Adeyemi; Haron, Razali (2017)
Since the introduction of Shariah status company in Bursa Malaysia in 1997, the demand for Shariah compliant investment has been increased. However, the limitations in Shariah compliant investment create worries and doubtfulness among the investors whether the Shariah compliant stocks performance can outperform the Non Shariah compliant stocks and the most important, maximizing the profit. Hence, this study is conducted using 40 Shariah and 40 non Shariah penny stocks as the samples. Then, technical analysis is applied to determine the market timing. From the technical analysis on Kuala Lumpur Composite Index (KLCI), the period chosen from April 2009 to July 2017. This study investigates about the significant differences between risk and return. By using independent sample T test for parametric data and Mann Whitney U test for non-parametric data, the result shows that there are no significant difference in terms of risk and return between Shariah penny stock portfolio and Non Shariah penny stock portfolio. Then, risk adjusted return measurements; Sharpe Ratio, Treynor Ratio and Jensen’s Alpha are employed to calculate risk adjusted return. From the result, Shariah penny stocks portfolio is better in terms of risk adjusted return ratios compared to the conventional portfolio.